(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the effectiveness of Task-Based Learning (TBL) in enhancing speaking fluency in English as a Foreign Language (EFL) classrooms. Unlike traditional grammar-focused instruction, TBL emphasizes communicative, student-centered activities that foster authentic language use. Through diverse task-based activities—such as problem-solving, discussions, and role-plays—students gain extensive exposure to real-world speaking practice. The study examines how TBL enhances confidence, promotes spontaneous speech, and develops overall oral proficiency. Additionally, it presents an analysis of classroom-based research and student feedback to evaluate the practical outcomes of TBL in EFL contexts.